Strategi Penerimaan Peserta Didik Baru Di SD Muhammadiyah Program Khusus Boyolali - PRAMACHINTYA, Destyana Ratih; , Prof. Dr. Bambang Sumardjoko; , Drs. Budi Sutrisno, M.Pd (2015)
The aim of the research is to describe the acceptance strategy to new students in Special Program of Muhammadiyah's Elementary School Boyolali. The sub focus of acceptance strategy of new students, the process of acceptance strategy of new students and the efforts which have been done to maintain the process of acceptance strategy of new students in Special Program of Muhammadiyah's Elementary School Boyolali. The research used descriptive qualitative. The strategy of the research used single strategy. The data source was obtained from informants, events and documents. Sampling technique used was purposive sampling. The data collection techniques used was interview, observation and documents analysis. To obtain the data validity in the research, the researcher used data triangulation. Meanwhile, data analysis technique used interactive analysis model. Based on the result of the research, can be concluded that: 1) the preparation of teaching and learning process in Special Program of Muhammadiyah's Elementary School Boyolali consisted of: a) the committee arrangement of the acceptance of new students (Penerimaan Peserta Didik Baru or PPDB), b) the arrangement of work program of the acceptance of new students comitee, c) the preparation of adiminstration documents or files, d) the preparation of infrastructure of the acceptance of new students. 2) The process of the acceptance of new students in Special Program of Muhammadiyah's Elementary School Boyolali consisted of: a) the determination of the implementation stage of the acceptance of new students: the retrieval of the registration form and filling the forms , b) the implementation of observation test of new students (spoken and written), c) the implementation of interview test of parents from new students, d) the selection process and assessment of observation test, e) the announcement of the acceptance result of new students, f) the administration of pre-register activity of the accepted new students. 3) The efforts done to maintain the acceptance process of new students in Special Program of Muhammadiyah's Elementary School Boyolali: a) doing the preparation of the acceptance of new students earlier, b) enhancing the quantity of students by doing the promotion, c) maintaining a good relationship with the society, d) fostering active communication and discussion with the foundation leader of branch Muhammadiyah ( Pimpinan Cabang Muhammadiyah or PCM), e) improving of the quality of schools and the human resources.